Oxford handbook of public health practice - Kawachi, Ichirō; Lang, Iain (Lecturer in public health); Ricciardi, Walter (New York, NY : Oxford University Press, 2020)
"Fully revised and updated for the fourth edition, the award-winning Oxford Handbook of Public Health Practice remains the first resort for practitioners in the field. Structured into practical sections addressed towards professional competencies and translating evidence into policy, this Handbook provides concise summaries and covers real issues from across the globe, providing a world of experience at your fingertips. Easy-to-use, concise, and practical, this Handbook is divided into seven parts that focus on the vital areas of this broad discipline. Reflecting recent advances, the most promising developments in the practice of public health are presented, along with essential summaries of the core disciplines. Specific sections are devoted to the development of professional competencies including negotiation, communicating risk to the public, community action, and translating evidence into policy. This Handbook will assist students, trainees, and practitioners around the world with its enriched information on the management of disasters, epidemics, health behaviour, acute and chronic disease prevention, community and government action, environmental health, vulnerable populations, and more"--
Revised edition of: Oxford handbook of public health practice / edited by Charles Guest ... [et al.]. 3rd ed. 2013.
Includes bibliographical references and index.
Keywords: Public health -- Handbooks, manuals, etc; Medicine, Preventive -- Handbooks, manuals, etc; Medical care -- Handbooks, manuals, etc